Condylar fracture in a paediatric patient undergoing conservative and functional treatment: Case report (Research, Society and Development, 2021)
Trauma to the jaw can lead to fracture of the mandibular condyle. Prevalence in children is low and treatment should focus on possible long-term effects on facial bone and soft tissue growth. Trauma can result in dysfunction, facial asymmetry, mandibular retraction, dysfunction and stiffness of the temporomandibular joint. Clinical examination and imaging tests are essential to obtain an accurate diagnosis and an effective treatment to avoid possible complications. Treatment can be surgical or non-surgical, but non-surgical treatment is the method of choice in most cases. The aim of this study is to report a case of mandibular condylar fracture in a pediatric patient who underwent conservative and functional care who, with adequate monitoring by the Maxillofacial Surgery and Traumatology team and family, showed complete remodeling of the fractured bone and total recovery of the dental occlusion. Treatment in pediatric patients through conservative management allows an adequate range of mandibular movement and remodeling at the fracture site, but patient and family adherence to treatment is very important to obtain good results.